Buzz Group Technique to Increase Writing Skill at EFL Students of Junior High School in Indonesia - Rizal Arisman (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
This research aimed to find out whether there was a significant difference of writing skill achievement between EFL students who were taught using Buzz Group technique and those who were taught using a conventional method by expecting the Buzz Group technique improved EFL students’ writing skill achievement at SMP Negeri 7 Baubau, Southeast Sulawesi. Design of this research was a quasi-experimental in which there were 22 students in both control and experimental groups. The findings of this research obtained: 1) the mean score of EFL students’ writing skill at pretest in experimental class was 51.09 in low category and the mean score of posttest was 72.18 in high category; 2) the mean score of EFL students’ writing skill at pretest in control class was 49.82 in low category and the mean score of posttest was 56.36 in moderate category; 3) the score of Asymp. Sig. (2-tailed) from hypothesis test was 0.000 in which it was less than 0.05. Therefore, this research concluded that there was a significant difference between of writing skill achievement between EFL students who were taught using Buzz Group technique and those who were taught using the conventional method at SMP Negeri 7 Baubau. In addition, the use of Buzz Group technique is better than the conventional method to improve EFL students’ writing skill achievement.